Modified nanofiltration membrane as well as preparation method and application thereof

The modified nanofiltration membrane with the polyamide active layer was formed through interface polymerization technology, which solved the problem of low iodine ion removal efficiency in the prior art, achieved efficient and economical iodine ion removal effect, and provided new ideas for the iodine removal technology of nanofiltration membrane.

CN119838438APending Publication Date: 2025-04-18TSINGHUA UNIVERSITY +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510122671.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The prior art methods for efficiently removing iodine ions in water bodies are not yet mature, especially in the field of nanofiltration membrane separation, nanofiltration membranes with small pore sizes and high negative charges on the surface are difficult to achieve economical and efficient iodine ions removal.

Method used

By using piperazine and triformyl chloride as aqueous and oil phase monomers, interfacial polymerization is carried out in the aqueous and oil phases, respectively, to form a polyamide active layer. By optimizing the interfacial polymerization reaction conditions and the pore size of the support material, the reaction site of the PIP is adjusted to change its protonation degree, thereby improving the iodine ion retention rate of the nanofiltration membrane.

Benefits of technology

A modified nanofiltration membrane with an iodine ion retention rate of 76.7% was achieved, combining efficient iodine removal performance and high pure water flux, providing a new idea for the development of nanofiltration membrane iodine removal technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119838438A_ABST
    Figure CN119838438A_ABST
Patent Text Reader

Abstract

The invention discloses a modified nanofiltration membrane as well as a preparation method and application thereof. The method comprises the following steps: S1, dissolving a water-phase monomer in deionized water to obtain a water-phase monomer solution; dissolving acyl chloride in an organic solvent to obtain an oil-phase monomer solution; s2, pretreating an ultrafiltration base membrane, immersing the pretreated ultrafiltration base membrane in the water-phase monomer solution, standing, draining redundant solution in the ultrafiltration base membrane, and drying; and S3, immersing the ultrafiltration base membrane in the step S2 in the oil-phase monomer solution, standing for interfacial polymerization reaction, placing the ultrafiltration base membrane in air for 1-2 minutes, and carrying out heat treatment to obtain the modified nanofiltration membrane. The invention provides a simple strategy to optimize the iodide ion removal performance of the nanofiltration membrane, and constructs the nanofiltration membrane on the base membranes with different pore diameters for verification, thereby providing a new thought for designing and developing the nanofiltration membrane for removing iodine in the future.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of nanofiltration membrane technology, and specifically to a method for preparing a modified nanofiltration membrane for efficient iodine removal based on interfacial polymerization protonation regulation and its application in iodine ion treatment in water bodies. Background Art

[0002] Iodine is an essential element for the human body and most mammals to maintain physiological functions and is widely present in nature. Its deficiency can lead to a decrease in the level of thyroid hormone in the human body, which in turn causes intellectual and physical developmental disorders. However, excessive iodine exposure can also cause a series of health problems such as hypothyroidism and hyperthyroidism. Generally speaking, the iodine concentration in most land areas is less than 10μg / L, so the risk of excessive iodine exposure to the human body is low. However, in some areas at home and abroad, high iodine concentrations have become an important issue worthy of close attention. Ruoqi Ma et al. mapped the distribution of iodine in groundwater across the country and showed that the risks associated with high-iodine groundwater are concentrated in marine encroachment areas exacerbated by excessive land use and intensive human over-exploitation. The inorganic iodine in groundwater is mainly in the form of iodine ions (I - ) accounts for more than 95% of the total iodine concentration, iodate (IO3 - ) and active iodine (I2 and HOI) account for a relatively low proportion. At present, common methods for removing iodine include ion exchange, chemical precipitation, adsorption and membrane separation. There is still a lack of mature processes for removing iodine ions from drinking water worldwide.

[0003] Membrane separation technology has become a commonly used method for removing complex pollutants in water treatment due to its characteristics of no phase change, low energy consumption, simple equipment, and easy operation. Reverse osmosis (RO), nanofiltration (NF), and reverse electrodialysis (RED) can all remove iodide ions from water. RO can separate and remove more than 71% of the total iodine in seawater. However, its cost is relatively high and it is only suitable for use in small water supply plants. NF is limited by its poor separation effect on monovalent ions and is rarely used in the field of iodine separation. Therefore, it is a very meaningful study to synthesize a nanofiltration membrane with a small pore size and a high negative surface charge to achieve economical and efficient removal of iodine ions in drinking water. Summary of the invention

[0004] The following is an overview of the subject matter described in detail herein. This overview is not intended to limit the scope of protection of this application.

[0005] In order to strengthen the application of nanofiltration in the treatment of iodine-containing wastewater, the nanofiltration (NF) membrane needs to have a smaller pore size and a high negative charge density. This application uses piperazine (PIP) as an aqueous phase monomer and trimesoyl chloride (TMC) as an oil phase monomer to form a polyamide layer by interfacial polymerization. In order to obtain a NF membrane surface with higher iodine ion separation performance, this application optimizes the interfacial polymerization reaction conditions (PIP, TMC concentration and interfacial polymerization reaction time) and the pore size of the supporting material (10KDa, 50KDa and 150KDa), so that the thickness of the polyamide active layer is thickened. By further adjusting the reaction site of PIP and changing the protonation degree of PIP, a modified NF membrane with a higher iodine ion rejection rate is obtained under the premise of flux recovery, and a NF membrane is constructed on a base membrane of different pore sizes for verification, which provides a new idea for the future design and development of NF membrane deiodine.

[0006] In order to achieve the above objectives, this application provides the following technical solutions:

[0007] The first aspect of the present application provides a method for preparing a modified nanofiltration membrane, wherein the modified nanofiltration membrane comprises an ultrafiltration base membrane and a polyamide active layer stacked on the surface of the ultrafiltration base membrane, wherein the polyamide active layer is obtained by interfacial polymerization of aqueous phase monomers and acyl chlorides.

[0008] In an exemplary embodiment, the method comprises the following steps:

[0009] S1. dissolving the aqueous monomer in deionized water to obtain an aqueous monomer solution; dissolving the acyl chloride in an organic solvent to obtain an oil phase monomer solution;

[0010] S2. The ultrafiltration base membrane is pretreated and immersed in the aqueous monomer solution, allowed to stand, and the excess solution in the ultrafiltration base membrane is drained and dried;

[0011] S3. Immerse the ultrafiltration base membrane in step S2 in the oil phase monomer solution, let it stand for interfacial polymerization reaction, place the ultrafiltration base membrane in the air for 1-2 minutes, and obtain the modified nanofiltration membrane after heat treatment.

[0012] In an exemplary embodiment, the concentration of the aqueous monomer solution is 0.1-2 wt %; for example, 0.1-0.2 wt %, 0.2-0.8 wt %, 0.8-1.2 wt %, 1.2-1.6 wt %, 1.6-2 wt %, etc. or any two values ​​as the range between the endpoint values, but are not limited to the listed values, and other values ​​not listed within the numerical range are also applicable;

[0013] Preferably, the concentration of the aqueous monomer solution is 0.2-0.8 wt %;

[0014] More preferably, the concentration of the aqueous monomer solution is 0.8 wt %.

[0015] In an exemplary embodiment, the concentration of the oil phase monomer solution is 0.1-0.15wt%; for example, 0.1-0.1.12wt%, 0.12-0.13wt%, 0.13-0.14wt%, 0.14-0.15wt%, etc. or any two values ​​as the range value between the endpoint values, but are not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable;

[0016] Preferably, the concentration of the oil phase monomer solution is 0.15 wt %.

[0017] In an exemplary embodiment, the reaction temperature of the interfacial polymerization reaction is room temperature, and the reaction time is 30-120 s; for example, 30-60 s, 60-90 s, 90-120 s, etc. or any two values ​​are used as range values ​​between the endpoint values, but are not limited to the listed values, and other values ​​not listed in the numerical range are also applicable;

[0018] Preferably, the interfacial polymerization reaction time is 30-60s;

[0019] More preferably, the interfacial polymerization reaction time is 60 s.

[0020] In an exemplary embodiment, the molecular weight cutoff of the ultrafiltration base membrane is 10-150KDa; for example, 10KDa, 50KDa, 100KDa, 150KDa, etc. or any two values ​​as the range value between the endpoint values, but are not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0021] In an exemplary embodiment, step S1 further comprises acidification of the aqueous monomer solution, wherein the acidification comprises: adjusting the pH of the aqueous monomer solution to 7-11 with an acid solution; for example, 7, 8, 9, 10, 11, etc. or any two values ​​as the range value between the endpoint values, but not limited to the listed values, and other values ​​not listed in the numerical range are also applicable;

[0022] Preferably, the pH of the aqueous monomer solution is 9-11;

[0023] More preferably, the pH of the aqueous monomer solution is 9.

[0024] In an exemplary embodiment, the aqueous phase monomer is selected from any one or more combinations of the following: piperazine, m-phenylenediamine, ethylenediamine, polyethyleneimine, o-phenylenediamine, p-phenylenediamine, propylenediamine, butylenediamine and pentamethylenediamine.

[0025] In an exemplary embodiment, the polyethyleneimine is selected from any one or more of polyethyleneimine 600, polyethyleneimine 1800, polyethyleneimine 10000, and polyethyleneimine 70000.

[0026] In an exemplary embodiment, the aqueous phase monomer is piperazine.

[0027] In an exemplary embodiment, the acyl chloride is selected from any one or more of phthaloyl chloride, isophthaloyl chloride, terephthaloyl chloride, trimesoyl chloride, pyromellitoyl chloride, adipoyl chloride and azelaoyl chloride;

[0028] Preferably, the acyl chloride is trimesoyl chloride.

[0029] In an exemplary embodiment, the organic solvent is selected from at least one of n-hexane, cyclohexane, n-heptane, toluene, xylene, and benzene;

[0030] Preferably, the organic solvent is n-hexane.

[0031] In an exemplary embodiment, the acid is selected from any one of sulfuric acid, hydrochloric acid, nitric acid, and phosphoric acid.

[0032] In an exemplary embodiment, the ultrafiltration base membrane is a polyethersulfone ultrafiltration base membrane.

[0033] In an exemplary embodiment, in step S2, the standing time is 1-2 minutes;

[0034] Preferably, the standing time is 2 minutes.

[0035] In an exemplary embodiment, in step S2, the drying includes: using an air gun to dry for 30 seconds to 1 minute until there are no obvious droplets on the surface;

[0036] Preferably, air gun drying is used for 1 min until there are no obvious droplets on the surface.

[0037] In an exemplary embodiment, in step S3, the heat treatment includes: placing the ultrafiltration base membrane in an oven for heating and curing.

[0038] In an exemplary embodiment, the heat treatment temperature is 50-80° C. and the time is 3-10 minutes;

[0039] Preferably, the temperature of the heat treatment is 60°C;

[0040] Preferably, the heat treatment time is 5 minutes.

[0041] In an exemplary embodiment, in step S3, the ultrafiltration base membrane is placed in air for 2 minutes.

[0042] In an exemplary embodiment, in step S2, the pretreatment includes: placing the ultrafiltration base membrane in a 5-30 wt % isopropanol aqueous solution for 10-30 min;

[0043] Preferably, the concentration of the isopropanol aqueous solution is 20wt%;

[0044] Preferably, the pretreatment time is 15 min.

[0045] In an exemplary embodiment, the thickness of the polyamide active layer is 1-200 nm.

[0046] In an exemplary embodiment, the modified nanofiltration membrane is stored in deionized water.

[0047] The second aspect of the present application provides a modified nanofiltration membrane prepared by the above method.

[0048] In an exemplary embodiment, the pore size of the modified nanofiltration membrane is 0.39-0.49 nm, and the pure water flux is 2.27-6.53 Lm -2 ·h -1 bar -1 The Zeta potential of the membrane surface is -12.5mV~-34.4mV at pH=7, and the maximum iodide ion retention rate is 76.7%.

[0049] In an exemplary embodiment, the pore size of the modified nanofiltration membrane is 0.39 nm, and the pure water flux is 3.17 L m -2 ·h -1 bar -1 The Zeta potential of the membrane surface is -34.4 mV at pH = 7.

[0050] The third aspect of the present application provides an application of the above-mentioned modified nanofiltration membrane in treating iodine-containing wastewater.

[0051] In an exemplary embodiment, the pore size of the modified nanofiltration membrane is 0.39-0.49 nm, and the pure water flux is 2.27-6.53 Lm -2 ·h -1 bar -1 The Zeta potential of the membrane surface is -12.5mV~-34.4mV at pH=7, and the maximum iodide ion retention rate is 76.7%.

[0052] In an exemplary embodiment, the pore size of the modified nanofiltration membrane is 0.39 nm, and the pure water flux is 3.17 L m -2 ·h -1 bar -1 The Zeta potential of the membrane surface is -34.4 mV at pH = 7.

[0053] In an exemplary embodiment, the modified nanofiltration membrane is prepared by the above method.

[0054] The fourth aspect of the present application provides a method for treating iodine-containing wastewater, wherein the method uses the modified nanofiltration membrane for nanofiltration treatment, and during the filtration process, the pre-pressing time is 30-60 minutes and the pressure is 1-4 bar;

[0055] Optionally, the pre-pressing time is 30 min;

[0056] Optionally, the pressure is 4 bar.

[0057] Compared with the existing related technologies, this application has the following technical effects:

[0058] The increase in the concentration of the aqueous phase monomers piperazine and benzoyl chloride monomers and the interfacial polymerization reaction time is conducive to the formation of a dense polyamide active layer; the ultrafiltration base membrane is conducive to the reduction of the pore size and the increase of the negative charge of the polyamide layer on the surface of the modified nanofiltration membrane; the acidification of the aqueous phase monomer solution controls the protonation degree of the aqueous phase monomer solution, increases the negative charge on the surface of the modified nanofiltration membrane, and improves the water permeability of the membrane surface. Specifically:

[0059] The present application first forms a thicker polyamide active layer by adjusting the concentrations of piperazine and phenylacyl chloride monomers and the interfacial polymerization reaction time, and then performs interfacial polymerization reaction on ultrafiltration base membranes with different pore sizes to form a denser and more negatively charged polyamide active layer surface, and finally adjusts the reaction site of piperazine to change the protonation degree of PIP, thereby further improving the negative charge on the membrane surface on the basis of restoring the water permeability, and obtaining a modified nanofiltration membrane with an iodide ion retention rate of 76.7%.

[0060] Other features and advantages of the present application will be described in the following description, and partly become apparent from the description, or be understood by implementing the present application. Other advantages of the present application can be realized and obtained by the schemes described in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] The accompanying drawings are used to provide an understanding of the technical solution of the present application and constitute a part of the specification. Together with the embodiments of the present application, they are used to explain the technical solution of the present application and do not constitute a limitation on the technical solution of the present application.

[0062] Figure 1 This is a comparison chart of the Zeta potential of the membrane materials prepared in the examples of this application;

[0063] Figure 2 This is a comparison chart of the molecular weight cutoff of membrane materials prepared in the examples of this application;

[0064] Figure 3This is a comparison chart of the pure water flux and salt (NaI and Na2SO4) retention rate of the membrane materials prepared in the examples of this application. DETAILED DESCRIPTION

[0065] In order to make the purpose, technical scheme and advantages of the present application clearer, the embodiments of the present application will be described in detail below. Examples of these preferred embodiments are illustrated in the accompanying drawings. The embodiments of the present invention shown in the accompanying drawings and described according to the accompanying drawings are merely exemplary, and the present application is not limited to these embodiments.

[0066] In the present application, unless otherwise specified, all preparation raw materials / components are commercially available products well known to those skilled in the art.

[0067] An embodiment of the present application provides a method for preparing a modified nanofiltration membrane for efficient iodine removal based on interfacial polymerization protonation regulation, wherein the modified nanofiltration membrane comprises an ultrafiltration base membrane and a polyamide active layer stacked on the surface of the ultrafiltration base membrane, wherein the polyamide active layer is obtained by interfacial polymerization of aqueous phase monomers and acyl chlorides.

[0068] As an embodiment of the present application, the ultrafiltration base membrane is used as a base membrane, and the ultrafiltration base membrane is selected from any one of polyethersulfone ultrafiltration membrane, polyacrylonitrile ultrafiltration membrane, polyvinylidene fluoride ultrafiltration membrane or polystyrene ultrafiltration membrane; preferably, it is a polysulfone ultrafiltration base membrane, but the present application is not limited to polysulfone material, and those skilled in the art can select specifically from the organic membrane materials in the prior art according to specific needs.

[0069] As an embodiment of the present application, the molecular weight cutoff of the ultrafiltration base membrane is 10-150KDa; preferably 10KDa, 50KDa, 150KDa; more preferably 10KDa and 150KDa.

[0070] As an embodiment of the present application, the aqueous phase monomer is selected from one or more of piperazine, m-phenylenediamine, ethylenediamine, polyethyleneimine, o-phenylenediamine, p-phenylenediamine, propylenediamine, butylenediamine and pentamethylenediamine; the polyethyleneimine is selected from one or more of polyethyleneimine 600, polyethyleneimine 1800, polyethyleneimine 10000 and polyethyleneimine 70000; preferably, the aqueous phase monomer is piperazine.

[0071] As an embodiment of the present application, the acyl chloride is selected from one or more of phthaloyl chloride, isophthaloyl chloride, terephthaloyl chloride, trimesoyl chloride, pyromellitoyl chloride, adipic acid chloride and azelaic acid chloride; preferably, the acyl chloride is trimesoyl chloride.

[0072] As an embodiment of the present application, the method comprises the following steps:

[0073] S1. dissolving the aqueous monomer in deionized water to obtain an aqueous monomer solution; dissolving the acyl chloride in an organic solvent to obtain an oil phase monomer solution;

[0074] S2. The ultrafiltration base membrane is pretreated and immersed in the aqueous monomer solution, allowed to stand, the excess solution in the ultrafiltration base membrane is drained and dried;

[0075] S3. Immerse the ultrafiltration base membrane in step S2 in the oil phase monomer solution, let it stand for interfacial polymerization reaction, place the ultrafiltration base membrane in the air for 1-2 minutes, and obtain the modified nanofiltration membrane after heat treatment.

[0076] As an embodiment of the present application, the concentration of the aqueous monomer solution is 0.1-2 wt %, preferably, the concentration is 0.2-0.8 wt %, and more preferably, the concentration is 0.8 wt %.

[0077] As an embodiment of the present application, the organic solvent is selected from at least one of n-hexane, cyclohexane, n-heptane, toluene, xylene, and benzene; preferably, the organic solvent is n-hexane.

[0078] As an embodiment of the present application, the concentration of the oil phase monomer solution is preferably 0.1-0.15 wt %, and the concentration of the oil phase monomer solution is preferably 0.15 wt %.

[0079] As an embodiment of the present application, the temperature of the interfacial polymerization reaction is room temperature, and the reaction time is 30-120 s; preferably, the reaction time is 30-60 s, and more preferably, the reaction time is 60 s.

[0080] As an embodiment of the present application, step S1 further includes acidification of the aqueous monomer solution, and the acidification includes: adjusting the pH of the aqueous monomer solution to 7-11 with an acid solution; preferably, to 9-11; more preferably, to 9.

[0081] As an embodiment of the present application, the acid solution is selected from any one of sulfuric acid, hydrochloric acid, nitric acid, and phosphoric acid.

[0082] As an embodiment of the present application, in step S2, the pretreatment includes: placing the ultrafiltration base membrane in a 5-30wt% isopropanol aqueous solution for 10-30min; preferably, optionally, the concentration of the isopropanol aqueous solution is 20wt%, and the pretreatment time is 15min.

[0083] As an embodiment of the present application, in step S2, the standing time is 1-2 minutes; preferably, the standing time is 2 minutes.

[0084] As an embodiment of the present application, in step S2, the drying includes: using an air gun to dry for 30 seconds to 1 minute until there are no obvious droplets on the surface; preferably, using an air gun to dry for 1 minute until there are no obvious droplets on the surface.

[0085] As an embodiment of the present application, in step S3, the ultrafiltration base membrane is placed in the air for 2 minutes.

[0086] As an embodiment of the present application, in step S3, the heat treatment includes: placing the ultrafiltration base membrane in an oven for heating and curing, wherein the heat treatment temperature is 50-80°C; the time is 3-10 minutes; preferably, the heat treatment temperature is 60°C; the heat treatment time is 5 minutes.

[0087] As an embodiment of the present application, the thickness of the polyamide active layer is 1-200 nm.

[0088] As an embodiment of the present application, the high-efficiency iodine-removing nanofiltration membrane prepared in the present application is preferably stored in deionized water.

[0089] The embodiment of the present application provides a modified nanofiltration membrane, the pore size of the modified nanofiltration membrane is 0.39-0.49nm; the pure water flux is 2.27-6.53L m-2·h-1·bar-1; the Zeta potential of the membrane surface is -12.5mV to -34.4mV at pH=7, and the maximum retention rate of iodide ions is 76.7%.

[0090] As an example of the present application, the pore size of the modified nanofiltration membrane is 0.39 nm, and the pure water flux is 3.17 L m -2 ·h -1 bar -1 The Zeta potential of the membrane surface is -34.4 mV at pH = 7.

[0091] An embodiment of the present application provides an application of the above-mentioned modified nanofiltration membrane in treating iodine-containing wastewater.

[0092] As an example of the present application, the pore size of the modified nanofiltration membrane is 0.39-0.49 nm, and the pure water flux is 2.27-6.53 Lm -2 ·h -1 bar -1 The Zeta potential of the membrane surface is -12.5mV~-34.4mV at pH=7, and the maximum iodide ion retention rate is 76.7%.

[0093] As an example of the present application, the pore size of the modified nanofiltration membrane is 0.39 nm, and the pure water flux is 3.17 L m -2 ·h -1 bar -1The Zeta potential of the membrane surface is -34.4 mV at pH = 7.

[0094] As an embodiment of the present application, the modified nanofiltration membrane is prepared by the above method.

[0095] The embodiment of the present application also provides a method for treating iodine-containing wastewater, wherein the method uses the above-mentioned modified nanofiltration membrane for nanofiltration treatment. During the filtration process, the pre-pressing time is 30-60 minutes and the pressure is 1-4 bar.

[0096] As an example of the present application, the pre-pressing time is 30 minutes and the pressure is 4 bar. The performance (retention rate, pure water flux) of the high-efficiency iodine removal nanofiltration membrane prepared in the present application is measured by a dead-end filtration device, comprising the following steps: firstly assembling the membrane into an ultrafiltration cup with the front side facing upward, adding ultrapure water and pre-pressing for 30 minutes at a stable pressure of 3 bar, and testing and calculating the pure water permeability (J, L m -2 ·h -1 bar -1 ); secondly, the raw material solution was added thereto for filtration to examine the retention rate of the membrane (R, %).

[0097] In the present application, the raw material solution required for the test includes inorganic salts NaI and Na2SO4, and the mass content of the inorganic salt ions is preferably 0.5-2g L -1 , specifically 2 g L -1 .

[0098] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0099] Example 1

[0100] 1) dissolving piperazine (PIP) in deionized water to prepare a 0.2 wt% aqueous monomer solution of piperazine (pH=11); using n-hexane solution to prepare a 0.1 wt% trimesoyl chloride (TMC) solution as an oil phase monomer solution;

[0101] 2) using a polyethersulfone (PES) ultrafiltration membrane with a molecular weight cutoff of 150 KDa (Microdyn Nadir, Xiamen, China) as the base membrane;

[0102] 3) Fix the PES ultrafiltration base membrane after 20wt% IPA pretreatment for 15min in the reactor, pour in 0.2wt% PIP aqueous solution, let stand for 2min, drain the PIP solution, and dry with an air gun for 1min to remove the residual PIP droplets. Then pour in 0.1wt% n-hexane TMC and let stand for 30s. Then, pour out the excess solution, leave it in the air for 2min, and then put the membrane into an oven at 60℃ for 5 minutes to cure, to obtain a nanofiltration membrane;

[0103] 4) The nanofiltration membrane was stored in ultrapure water at 4°C for subsequent experiments.

[0104] Example 2

[0105] The preparation method of this invention is different from that of Example 1 in that the concentration of the PIP solution is 0.8 wt %, the concentration of the TMC solution is 0.1 wt %, and the interfacial polymerization reaction time is 30 s.

[0106] Example 3

[0107] The preparation method is basically the same as that of Example 1, except that the concentration of the PIP solution is 0.8 wt %, the concentration of the TMC solution is 0.15 wt %, and the interfacial polymerization reaction time is 30 s.

[0108] Example 4

[0109] 1) dissolving piperazine (PIP) in deionized water to prepare a 0.8 wt% aqueous monomer solution of piperazine (pH=11); using n-hexane solution to prepare a 0.15 wt% trimesoyl chloride (TMC) solution as an oil phase monomer solution;

[0110] 2) using a polyethersulfone (PES) ultrafiltration membrane with a molecular weight cutoff of 150 KDa (Microdyn Nadir, Xiamen, China) as the base membrane;

[0111] 3) The interfacial polymerization reaction time is 1 min;

[0112] 4) Fix the PES-based membrane after 20% IPA pretreatment for 15 minutes in the reactor, pour in PIP (0.8wt%) aqueous solution, let stand for 2 minutes, drain the PIP solution, and use an air gun to dry for 1 minute to remove the residual PIP droplets. Then pour in 0.15wt% n-hexane TMC and let stand for 1 minute. Then, pour out the excess solution, leave it in the air for 2 minutes, and then put the membrane into an oven at 60°C for 5 minutes to cure, and obtain a nanofiltration membrane;

[0113] 5) The nanofiltration membrane was stored in ultrapure water at 4°C for subsequent experiments.

[0114] Example 5

[0115] The preparation method of this example is basically the same as that of Example 4, except that a polyethersulfone (PES) ultrafiltration membrane (Microdyn Nadir, Xiamen, China) with a molecular weight cutoff of 10 KDa is used as a base membrane to prepare the nanofiltration membrane.

[0116] Example 6

[0117] 1) dissolving piperazine (PIP) in deionized water to prepare a 0.8 wt% aqueous monomer solution of piperazine; using n-hexane solution to prepare a 0.15 wt% trimesoyl chloride (TMC) solution as an oil phase monomer solution;

[0118] 2) using polyethersulfone (PES) ultrafiltration membrane with a molecular weight cutoff of 50 KDa (Microdyn Nadir, Xiamen, China) as the base membrane for the preparation of nanofiltration membrane;

[0119] 3) The nanofiltration membrane was prepared in the same manner as in Example 4;

[0120] 4) The nanofiltration membrane was stored in ultrapure water at 4°C for subsequent experiments.

[0121] Example 7

[0122] 1) dissolving piperazine (PIP) in deionized water to prepare a 0.8 wt% aqueous monomer solution of piperazine, and adjusting the pH of the PIP solution to 9 with an HCl solution; preparing a 0.15 wt% trimesoyl chloride (TMC) solution with an n-hexane solution as an oil phase monomer solution;

[0123] 2) using a polyethersulfone (PES) ultrafiltration membrane with a molecular weight cutoff of 10 KDa (Microdyn Nadir, Xiamen, China) as the base membrane;

[0124] 3) The interfacial polymerization reaction time is 1 min;

[0125] 4) Fix the PES-based membrane after 20% IPA pretreatment for 15 minutes in the reactor, pour in the acidified PIP (0.8wt%) aqueous solution, let stand for 2 minutes, drain the PIP solution, and use an air gun to dry for 1 minute to remove the residual PIP droplets. Then pour in 0.15wt% n-hexane TMC and let stand for 1 minute. Then, pour out the excess solution, leave it in the air for 2 minutes, and then put the membrane into an oven at 60°C for 5 minutes to cure, and obtain a nanofiltration membrane;

[0126] 5) The nanofiltration membrane was stored in ultrapure water at 4°C for subsequent experiments.

[0127] Example 8

[0128] The preparation method of this comparative example is basically the same as that of Example 7, except that the pH of the prepared acidified PIP solution is 10 and the concentration is 0.8 wt %.

[0129] Example 9

[0130] The preparation method of this comparative example is basically the same as that of Example 7, except that a polyethersulfone (PES) ultrafiltration membrane with a molecular weight cutoff of 50 KDa (Microdyn Nadir, Xiamen, China) is used as the base membrane.

[0131] Example 10

[0132] The preparation method of this comparative example is basically the same as that of Example 7, except that a polyethersulfone (PES) ultrafiltration membrane (Microdyn Nadir, Xiamen, China) with a molecular weight cutoff of 150 KDa is used as the base membrane.

[0133] Embodiment 11

[0134] The preparation method of this comparative example is basically the same as that of Example 7, except that the pH of the acidified PIP solution is 10, the concentration is 0.8 wt %, and a polyethersulfone (PES) ultrafiltration membrane (MicrodynNadir, Xiamen, China) with a molecular weight cutoff of 50 KDa is used as the base membrane.

[0135] Example 12

[0136] The preparation method of this comparative example is basically the same as that of Example 7, except that the pH of the acidified PIP solution is 10, the concentration is 0.8 wt %, and a polyethersulfone (PES) ultrafiltration membrane (MicrodynNadir, Xiamen, China) with a molecular weight cutoff of 150 KDa is used as the base membrane.

[0137] Test Example 1

[0138] Figure 1 The Zeta potential test results of the membrane products prepared in the embodiments of the present invention are as follows: Figure 1 It can be seen that with the increase of negative charge on the surface of the ultrafiltration base membrane, the negative charge on the surface of the nanofiltration membrane constructed thereon increases accordingly; and with the increase of the degree of PIP acidification, the negative charge on the surface of the nanofiltration membrane gradually increases.

[0139] Depend on Figure 2 It can be seen that the smaller the pore size of the base membrane, the smaller the pore size of the nanofiltration membrane constructed thereon, and the denser the polyamide active layer; when the protonation degree of PIP increases, the pore size of the nanofiltration membrane surface shows a slight downward trend, which makes the pure water flux recover. Among them, the membrane material prepared in Example 7 has the highest surface negative charge and a larger pore size.

[0140] Test Example 2

[0141] The test was conducted in a dead-end filtration system at 25±1°C and an operating pressure of 3 bar.-1 of NaI and 2 g L -1 The salt rejection rate of the membrane was determined by the Na2SO4. The experimental results are shown in Table 1 and Figure 3 shown.

[0142] Table 1 Nanofiltration membrane separation performance of different embodiments

[0143] Example <![CDATA[Pure water flux (L m -2 ·h -1 ·bar -1 )]]> NaI retention rate (%) <![CDATA[Sodium sulfate rejection rate (%)]]> Example 4 3.07±0.03 52.58±2.25 97.33±0.32 Example 5 2.27±0.06 60.01±1.8 98.02±0.71 Example 7 3.17±0.06 76.75±1.45 98.49±0.79 Example 1 6.53±0.11 10.68±2.3 85.6±1.43 Example 2 4.31±0.09 22.33±1.66 90.72±0.94 Example 3 3.35±0.12 40.68±1.3 95.01±0.66 Example 6 2.56±0.064 55.43±0.42 98.01±0.66 Example 8 2.21±0.05 73.27±1.48 98.46±0.46 Example 9 3.32±0.04 71.46±1.0 97.89±0.47 Example 10 3.56±0.06 69.05±1.63 97.02±0.64 Embodiment 11 2.66±0.05 65.6±2.32 97.41±0.89 Example 12 2.99±0.02 65.12±0.74 97.46±0.81

[0144] From Table 1 and Figure 3 It can be seen that: by optimizing the interfacial polymerization reaction conditions (PIP, TMC concentration and interfacial polymerization reaction time) and the pore size of the supporting material (10KDa, 50KDa and 150KDa), the iodide ion retention rate increased from 10.68% to 60%. On the contrary, this control condition will increase the thickness of the polyamide active layer, thereby greatly reducing the water permeability of the NF membrane surface. By adjusting the protonation degree of PIP, under the premise of flux recovery, a modified nanofiltration membrane with an iodide ion retention rate of 76.7% was further obtained, realizing precise control of interfacial polymerization. The membrane material prepared in Example 7 has a higher pure water flux and a stronger iodide ion retention capacity.

[0145] It can be seen from the above embodiments that the beneficial effect of the present invention is that, compared with the prior art, the present application provides a method for preparing a modified nanofiltration membrane for efficient iodine removal based on interfacial polymerization protonation regulation, explores a simple strategy to optimize the iodine ion removal performance of the nanofiltration membrane, and constructs nanofiltration membranes on base membranes of different pore sizes for verification, which provides a new idea for the future design and development of nanofiltration membrane iodine removal.

[0146] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing a modified nanofiltration membrane, characterized in that: The modified nanofiltration membrane comprises an ultrafiltration base membrane and a polyamide active layer stacked on the surface of the ultrafiltration base membrane, wherein the polyamide active layer is obtained by interfacial polymerization of aqueous phase monomers and acyl chlorides. The method comprises the following steps: S1. dissolving the aqueous monomer in deionized water to obtain an aqueous monomer solution; dissolving the acyl chloride in an organic solvent to obtain an oil phase monomer solution; S2. The ultrafiltration base membrane is pretreated and immersed in the aqueous monomer solution, allowed to stand, and the excess solution in the ultrafiltration base membrane is drained and dried; S3. immersing the ultrafiltration base membrane in step S2 in the oil phase monomer solution, allowing it to stand for interfacial polymerization, placing the ultrafiltration base membrane in air for 1-2 minutes, and obtaining the modified nanofiltration membrane after heat treatment; The concentration of the aqueous monomer solution is 0.1-2 wt %; the concentration of the oily monomer solution is 0.1-0.15 wt %; the reaction time of the interfacial polymerization reaction is 30-120 s; the molecular weight cutoff of the ultrafiltration base membrane is 10-150 KDa; Optionally, step S1 further comprises acidification of the aqueous monomer solution, wherein the acidification comprises: adjusting the pH of the aqueous monomer solution to 7-11 with an acid solution.

2. The method according to claim 1, characterized in that The aqueous phase monomer is selected from any one or more combinations of the following: piperazine, m-phenylenediamine, ethylenediamine, polyethyleneimine, o-phenylenediamine, p-phenylenediamine, propylenediamine, butylenediamine and pentamethylenediamine; and / or The acyl chloride is selected from any one or more of phthaloyl chloride, isophthaloyl chloride, terephthaloyl chloride, trimesoyl chloride, pyromellitoyl chloride, adipoyl chloride and azelaoyl chloride; and / or The organic solvent is selected from at least one of n-hexane, cyclohexane, n-heptane, toluene, xylene and benzene; and / or The acid solution is selected from any one of sulfuric acid, hydrochloric acid, nitric acid and phosphoric acid; and / or The ultrafiltration base membrane is a polyethersulfone ultrafiltration base membrane.

3. The method according to claim 2, characterized in that The polyethyleneimine is selected from any one or more of polyethyleneimine 600, polyethyleneimine 1800, polyethyleneimine 10000, and polyethyleneimine 70000.

4. The method according to any one of claims 1 to 3, characterized in that The concentration of the aqueous monomer solution is 0.2-0.8 wt %; and / or The pH of the aqueous monomer solution is 9-11; and / or In step S2, the standing time is 1-2 minutes; and / or In step S2, the drying includes: using an air gun to dry for 30 seconds to 1 minute until there are no obvious droplets on the surface; and / or The temperature of the interfacial polymerization reaction is room temperature, and the reaction time is 30-60s; and / or In step S3, the heat treatment comprises: placing the ultrafiltration base membrane in an oven for heating and curing, wherein the heat treatment temperature is 50-80° C. and the time is 3-10 minutes.

5. The method according to any one of claims 1 to 3, characterized in that The aqueous phase monomer is piperazine, the concentration of the aqueous phase monomer solution is 0.8 wt %, and the pH of the aqueous phase monomer solution is 9; the acyl chloride is trimesoyl chloride, the concentration of the oil phase monomer solution is 0.15 wt %, and the organic solvent is n-hexane; In step S2, the standing time is 2 minutes; In step S2, air gun drying is used for 1 min until there are no obvious droplets on the surface; The interfacial polymerization reaction time is 60s; In step S3, the ultrafiltration base membrane is placed in air for 2 minutes; In step S3, the heat treatment temperature is 60° C. and the heat treatment time is 5 minutes.

6. The method according to any one of claims 1 to 3, characterized in that In step S2, the pretreatment includes: placing the ultrafiltration base membrane in a 5-30wt% isopropanol aqueous solution for 10-30min; Optionally, the concentration of the isopropanol aqueous solution is 20wt%; Optionally, the pretreatment time is 15 min.

7. The method according to any one of claims 1 to 3, characterized in that The thickness of the polyamide active layer is 1-200 nm; and / or The modified nanofiltration membrane was stored in deionized water.

8. A modified nanofiltration membrane prepared by the method according to any one of claims 1 to 7, characterized in that: The pore size of the modified nanofiltration membrane is 0.39-0.49 nm; the pure water flux is 2.27-6.53 L m -2 ·h -1 bar -1 ; The Zeta potential of the membrane surface is -12.5mV~-34.4mV at pH=7.

9. Use of the modified nanofiltration membrane according to claim 8 in treating iodine-containing wastewater.

10. A method for treating iodine-containing wastewater, characterized in that: The method adopts the modified nanofiltration membrane described in claim 8 to perform nanofiltration treatment, wherein during the filtration process, the pre-pressing time is 30-60 minutes and the pressure is 1-4 bars.

Citation Information

Patent Citations

  • Asymmetric selective nanofiltration membrane and preparation method thereof

    CN115738745A

  • Nanofiltration membrane as well as preparation method and application thereof

    CN116510514A